The Potency of Ammonia from Broiler’s Manure Based on Age Phase of Ration Administration on Closed House and Open House - Mona Anggraini; Irma Badarina; Bieng Brata (Universitas Bengkulu, 2022)
The aim of this research was to evaluate the potency of ammonia production from broiler’s manure based on the age phase of ration administration on the closed and open house cage. This research used Completely Randomized Design in Factorial 3x 2 with the first factor was three age phase of rations administration (0-10 days old, 11-21 days old and 22-32 days old) with three replications of each age phases. The second factor was the type of cage system (closed and open house) with two cages of each cage type. The variable observed was the ammonia concentration from broiler’s manure. The Data were analyzed for their variance by Analyzes of Variance (Anova). The detailed test used Duncan Multiple Range Test. The result of this research showed that the age phases of ration administration increased the manure ammonia concentration (P<0.05). The older of age phase increased the ammonia concentration. The cage system had significant effect to ammonia concentration. The closed house system produced the ammonia concentration higher than open house cage. The technology that were used in closed house system had a positive effect to ammonia mitigation.